The Discrepancy Between Educational Management in São Paulo and Paulo Freire’s Studies - Silva, Hilda Maria Gonçalves [UNESP]; Dib, Aline Michelle (FapUNIFESP (SciELO), 2023)
This research examines the concept of teaching work within the São Paulo Basic Education System to identify its similarities and differences with Paulo Freire’s postulates regarding educational management. The analysis focused on the São Paulo Curriculum, a guiding document for teaching action. The study employed content analysis supported by the NVivo software to categorize the prevalent ideas in the document. The analysis delved into competence, engagement, and autono-my advocacy categories. Among the main findings, it is noteworthy to men-tion the contradictory stance of the São Paulo State Department of Education (SEESP), which presents a discourse aligned with Freirean premises while exhibiting a mechanistic teaching approach that reproduces neoliberal paradigms.
O Descompasso entre a Gestão da Educação Paulista e os Estu-dos de Paulo Freire. Esta pesquisa analisa a concepção de trabalho docente
Keywords: Currículo Paulista; Paulo Freire; Teaching Practice